Leadership Transformation Strategy in the Development of Halal Tourism Based on Local Wisdom in the Community of North Lombok Regency - Mahardani, Ahmad Subhan; Taqwiem, Ahsani (Jurnal Ilmiah Ekonomi Islam, 2024)
This research that aims to answer questions about community-based tourism development strategies and the role of leadership in community-based tourism village development in North Lombok Region, Lombok Island, West Nusa Tenggara. The method used in this study is a phenomenological-qualitative approach. The technique of collecting data is by means of interviews, documentation and direct observation to the Village Head as a leader, village government, tourism employees, and the Sekapuk village community to explore information and experiences in leadership roles. The results obtained indicate that the tourism business development strategy is in accordance with the Sambik Bangkol Village Regulation Number 06 of 2018 concerning the Sambik Bangkol Village Tourism Development Plan and uses the concept of community based tourism to involve the community's role in tourism management and development. Meanwhile, the leadership role in Sambik Bangkol has been carried out in accordance with Covey's leadership theory, namely: 1) pathfinding by setting and carrying out the vision, mission and tourism development goals, 2) aligning, namely by forming organizations and support groups to implement tourism development strategies, 3) Empowering namely by giving a role to the community as a form of community-based tourism concept as an effort to empower the community. Suggestions from this research are giving a role to the community in contributing to tourism so that it is improved and given fairly and equitably so that the community can also feel the benefits of Setigi tourism so that people can be productive and empowered.